Adaptive tracking algorithm of network attack signal in complex user environment. (17th February 2018) - Zhao, Bing; Guo, Gaiwen
Abstract: Because of the low signal to noise and poor tracking accuracy in network attack, the tracking process cannot be done well. To this end, a tracking algorithm of network attack signal based on Kalman filtering is proposed in this paper. Firstly, compressed sampling technique is used to obtain the time-domain signal samples in the signal node, to achieve the signal detection. Then, the adaptive tracking for network attack signal using the Kalman filtering tracking algorithm is used. The experimental results show that the colored noise analysis theory in the proposed algorithm, further improves the tracking accuracy of the attack signal, and the tracking performance of network attack signal.